Toward Zakat Management Integration in Indonesia: Problems and Solution - Arif Hidayatullah; Anita Priantina (AHKAM : Jurnal Ilmu Syariah, 2018)
The functions of zakat collection and distribution are carried out by both government and private institutions in Indonesia. As those institutions work without coordination, zakat integration become the main issue. This condition resulted in a zakat distribution gap. The center of economy such as Java may have significant zakat collection and zakat distribution , while remote area with limited resources and worse economic level may face both low zakat collection and zakat distribution. The enactment of Law No. 23 of 2011 concerning the Zakat Management brings hope for integration between government and private zakat operators. This study aims to find out the problems in implementing the Zakat Law, provide solutions and strategies to optimize the effort towards integrated zakat management. The method used in this research is the Analytic Network Process (ANP). The results indicate that there are two clusters of problems; internal and external. Internal issues sorted by priority order are: lack of human resources performance, lack of coordinator capacity, the different level of understanding, and lack of commitment of the zakat operators. External issues sorted by priority order are: lack of information technology development, lack of zakat management standard, lack of information dissemination, and lack of technical regulation. The solutions proposed to solve internal problems according to priority ranking are: coordinator capacity building, internal education on zakat integration, human resource monitoring and evaluation, and zakat operators’ commitment building.  Finally, according to the respondents, the solution proposed based on priority ranking are: zakat management SOP setting, zakat law information dissemination, IT system building, and zakat technical regulation.